O Livro de Jó na literarura brasileira: reflexões sobre resas do Diabo de Wenceslau de Queiroz - Santos, Petronio Matias dos (Universidade Federal de São Carlos, 2025)
This dissertation presents a critical reading of Rezas do Diabo (1939), by Wenceslau de Queiroz (1863–1921), by articulating elements of Brazilian Symbolism, the decadentist tradition, and literary Satanism, while also examining the critical reception of the text. It is based on the hypothesis that Rezas do Diabo represents a kind of rewriting of the Book of Job from the biblical tradition, inverting its spiritual logic and producing a “bible in reverse.” The main objective of this study is to recover and critically analyze Queiroz’s poetic work, placing it within the context of Brazilian Symbolist literature and investigating its critical reception over time. To this end, the research outlines a historical and conceptual panorama of Symbolism, from its origins in France—with authors such as Charles Baudelaire and the philosophical influences of Schopenhauer, Swedenborg, and Eduard von Hartmann—to its reception in Brazil. The study discusses how Symbolism incorporated elements of religious mysticism and Satanism as forms of critique against modern rationality, scientism, and bourgeois morality. Brazilian authors such as Cruz e Sousa, Alphonsus de Guimaraens, and Augusto dos Anjos are also highlighted throughout the analysis. As the study advances toward the work of Wenceslau de Queiroz, it seeks to recover biographical aspects, forgotten works, and pseudonyms used by the author, as well as his role as critic, professor, and writer. Focusing especially on Rezas do Diabo, the dissertation proposes a revaluation of the work through a critical reading that highlights its originality and aesthetic boldness. Ultimately, it aims to demonstrate how the book dialogues with the Faustian myth and subverts the traditional biblical narrative, employing resources such as synesthesia, allegory, and the grotesque to construct a provocative poetics. The final aim is to reaffirm Wenceslau de Queiroz’s relevance in Brazilian literature, positioning his work as an example of aesthetic resistance and questioning of religious, moral, and literary conventions.
The Book of Job in brazilian literature: reflections on the Devil's Roots by Wenceslau de Queiroz
Keywords: Simbolismo; Wenceslau de Queiroz; Rezas do Diabo; Mito do Fausto; Symbolism; Faust myth; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA BRASILEIRA; 4. Educação de Qualidade